2016
DOI: 10.1177/1040638716675197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different primer sets for sexing birds

Abstract: Because many bird species are monomorphic or only sexually dimorphic in adult stages, it is difficult to determine their sexes, which may cause significant problems in population and conservation studies. DNA-based sexing relies on the chromodomain helicase DNA binding ( CHD) gene located on the W chromosome and its homolog on the Z chromosome, giving distinct banding patterns on agarose gel as a result of length differences in intronic regions within this gene. We used 3 specific primer sets, CHD1F/CHD1R, 255… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 30 publications
4
55
1
2
Order By: Relevance
“…Similarly, according to agarose gel electrophoresis, the success rates of primer sets CHD1F/CHD1R, 2550F/2718R, and P2/P8 were 100% (n = 22), 100% (n = 22), and 40.90% (n =22) for blood samples; 100% (n = 2), 100% (n = 2), and 0 % (n = 2) for feather samples. This can be directly related to the fact that DNA in feather samples generally submit lower copy numbers than DNA obtained from blood [25] and it occurs for keratinous samples also. Another possibility is perhaps DNA from feather and keratinous samples may get more easily degraded [25], so the quality and quantity of DNA extracted from feather and keratinous material would be correspondingly low.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, according to agarose gel electrophoresis, the success rates of primer sets CHD1F/CHD1R, 2550F/2718R, and P2/P8 were 100% (n = 22), 100% (n = 22), and 40.90% (n =22) for blood samples; 100% (n = 2), 100% (n = 2), and 0 % (n = 2) for feather samples. This can be directly related to the fact that DNA in feather samples generally submit lower copy numbers than DNA obtained from blood [25] and it occurs for keratinous samples also. Another possibility is perhaps DNA from feather and keratinous samples may get more easily degraded [25], so the quality and quantity of DNA extracted from feather and keratinous material would be correspondingly low.…”
Section: Resultsmentioning
confidence: 99%
“…This can be directly related to the fact that DNA in feather samples generally submit lower copy numbers than DNA obtained from blood [25] and it occurs for keratinous samples also. Another possibility is perhaps DNA from feather and keratinous samples may get more easily degraded [25], so the quality and quantity of DNA extracted from feather and keratinous material would be correspondingly low. Another study reported that the polymorphic nature of the intron length, along with the power of variability in electrophoresis resolution, does not allow for accurate sex identification in some species of bird [14, 20,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although sex identification is very important for biological and ecological field studies, it is difficult to distinguish males and females of this species by the traditional method of inspecting external features, given that the species exhibits monomorphic characteristics. In other species, molecular sexing using PCR methods targeting the CHD1 gene has made it possible to identify the sex rapidly and accurately using non-invasive samples 6,7,13,14 . Japanese murrelets are morphologically monomorphic birds, meaning that it is hard to distinguish between males and females.…”
Section: Discussionmentioning
confidence: 99%